2020
DOI: 10.3390/genes11010094
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Genome of an Endogenous Nimavirus (Nimav-1_LVa) From the Pacific Whiteleg Shrimp Penaeus (Litopenaeus) Vannamei

Abstract: White spot syndrome virus (WSSV), the lone virus of the genus Whispovirus under the family Nimaviridae, is one of the most devastating viruses affecting the shrimp farming industry. Knowledge about this virus, in particular, its evolution history, has been limited, partly due to its large genome and the lack of other closely related free-living viruses for comparative studies. In this study, we reconstructed a full-length endogenous nimavirus consensus genome, Nimav-1_LVa (279,905 bp), in the genome sequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 80 publications
(132 reference statements)
0
15
0
Order By: Relevance
“…However, other markers of granular hemocytes, such as mannose-binding protein are negligibly detected in CC5, indicating CC5 might be immature granular hemocytes. Innexin, a gap junction protein, functions as an antiviral protein in Procambarus clarkia ( 43 ). Therefore, CC5 might be immature granular hemocytes involved in immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…However, other markers of granular hemocytes, such as mannose-binding protein are negligibly detected in CC5, indicating CC5 might be immature granular hemocytes. Innexin, a gap junction protein, functions as an antiviral protein in Procambarus clarkia ( 43 ). Therefore, CC5 might be immature granular hemocytes involved in immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the limited number of known exogenous nimaviruses, genomic analyses of decapod crustaceans have revealed the presence of sequences originating from nimaviruses (7)(8)(9)(10)(11). These endogenous viral elements (12,13) are present as multi-copy elements sometimes reaching hundreds of copies per haploid genome (7,10).…”
Section: Bdls01000001-bdls01000002 Lc741431)mentioning
confidence: 99%
“…The earliest reportson WSSV-like sequences in the penaeid shrimp genomes noted an expansion of a large DNA segment containing WSSV homologs as well as various eukaryotic genes, including baculoviral inhibitor of apoptosis repeat (BIR)-containing proteins (7) and an HSP70 homolog (17). Bao et al also observed the presence of eukaryotic-like genes on the Nimav-1_LVa genome (11). The availability of complete majaniviral genomes confirms that the presence of eukaryotic-like genes is a shared trait of majaniviruses.…”
Section: Majaniviruses Colonizie Telomere Repeats Of Penaeid Shrimp G...mentioning
confidence: 99%
See 2 more Smart Citations